A Novel Electrochemical Sensor for β2‐Agonists with High Sensitivity and Selectivity Based on Surface Molecularly Imprinted Sol‐gel Doped with Antimony‐Doped Tin Oxide. Issue 5 (3rd April 2014) - Lei, Rulin; Guo, Chunhui; Xiong, Huayu; Dong, Chao; Zhang, Xiuhua; Wang, Shengfu
Abstract A novel strategy to improve the sensitivity of molecularly imprinted polymer (MIP) sensors was proposed for the determination of β2‐agonists. The imprinted sol‐gel film was prepared by mixing silica sol with a functional monomer of antimony‐doped tin oxide (ATO) and a template of β2‐agonists. ATO, which was embedded in the surface of the molecularly imprinted sol‐gel film, not only provides the excellent conductivity for biosensor but also increases the stability and the surface area of the MIP film. The imprinted sensor was characterised by field emission scanning electron microscope, fourier transform infrared spectroscopy and electrochemical methods. Under the optimal experimental conditions, the peak current was linear with the logarithm of the concentration of clenbuterol (CLB) in the range of 5.5 nM–6.3 µM, and a detection limit of 1.7 nM was obtained. Meanwhile, the electrochemical sensor showed excellent specific recognition of the template molecule among structurally similar coexisting substances. Furthermore, the proposed sensor was satisfactorily applied to determine β2‐agonists in human serum samples. The good results indicated that highly effective molecularly imprinted sol‐gel films doped with ATO can be employed for other analytes.